Retrogradation of carbonate platforms on a rifted margin: the late Ediacaran record of the northwestern Yangtze Craton (SW China) - Xia, Maolong; Zhang, Benjian; Jia, Song; Zhao, Chunni; Feng, Mingyou; Shang, Junxin; Zhang, Chao; Li, Yong; Li, Yiwen (Frontiers in Earth Science, 2024)
The Late Ediacaran Dengying Formation, located in the Sichuan Basin of the northwestern Yangtze Craton, is of significant interest in oil and gas exploration due to its abundant pores and vugs within microbial mound-shoal complexes. However, there is still uncertainty regarding the spatiotemporal distribution and controlling factors of the platform margin. This study comprehensively analyzes the retrogradation pattern of the Dengying Formation platform margin using seismic data, well logs, field outcrops, and petrological characteristics. Our findings reveal that the Dengying Formation strata surrounding the rift basin at the northwestern of the Yangtze Craton can be divided into three main depositional facies: basin facies, slope facies, and platform margin facies. Additionally, based on the integration of lithological, log, and seismic characteristics, the Dengying Formation is subdivided into four third-order sequences, with five sequence boundaries and three seismic facies identified. Supported by sequence stratigraphy and geophysical data, we have reconstructed the tectono-sedimentary evolution of the multiple platform margins on the eastern side of the Deyang-Anyue rift in the Sichuan Basin during the late Ediacaran. Our findings indicate that the platform underwent two phases of retrogradation. The second-stage platform margin underwent retrogradation towards the interior, spanning a distance between 10 and 80 km, based on the initial configuration established by the first-stage platform margin. The main controls for progradation and retrogradation of carbonate platforms are eustatic sea-level changes and tectonic activity. Eustatic sea-level changes can be divided into constructive and destructive phases. Constructive phases are commonly observed in highstand systems tracts, while destructive phases are often associated with transgressive systems tracts and are related to platform retrogradation processes. However, sea-level changes alone cannot fully control the process of platform retrogradation. The thermal subsidence following mantle plume events likely played a significant role in the retrogradation of the platform in the study area. During this period, tectonic processes controlled the geometry of the platform and the deposition of carbonates in the platform margin-slope-basin environment. Additionally, karst-related mound-shoal complexes developed extensively along the platform margin of the Dengying Formation in the northwestern Yangtze Craton. The Lower Cambrian dark shales represent high-quality hydrocarbon source rocks, while the Dengying Formation exhibits an optimal source-reservoir configuration.